PENGGUNAAN PRINSIP INTERGENERATIONAL EQUITY DALAM PERLINDUNGAN HUKUM TERHADAP KESEJAHTERAAN HEWAN DI TEMPAT WISATA DARI KEKEJAMAN - Johana Ake Christianti (BELLI AC PACIS (Jurnal Hukum Internasional), 2021)
Good animal welfare occurs when the health, nutrition, behavior, environmental and psychological needs of animals are met. However, the captivity of wild animals by tourist attractions is often not able to meet the needs of these animals. In addition, the exhibition and training of wildlife by tourist sites is carried out through a process that results in unnecessary suffering. This legal research aims to analyze the legal protection of animal welfare from cruelty in tourist attractions based on the principle of Intergenerational Equity and to analyze the application of these principles in tourist attractions to the national laws of several countries (Indonesia and United Kingdom) in protecting animal welfare from cruelty. The results of this legal research show that: First, protection under existing international agreements has not been able to protect animal welfare from cruelty to the maximum, while the pure use of the principle of Intergenerational Equity cannot be the only source of international law to protectanimal welfare, especially in places travel. Second, Indonesian national law applies this principle more to animal welfare laws than national law of the United Kingdom does.